Analisis Pengaruh Kinerja Pegawai Dan Efektivitas Kepemimpinan Terhadap Kinerja Organisasi Pada Dinas Pendidikan Provinsi Maluku - Zainuddin Notanubun (Pattimura University, 2018)
The purpose of this study was to determine the effect of employee performance and leadership effectiveness on organizational performance in the Maluku Province Education Office. The sample in the study involved 276 employees from the education office, as well as the Regional Office of the Ministry of Education and Culture collected through survey methods and analyzed using causal correlational techniques. The results indicate that there is a significant influence between employee performance and leadership effectiveness on organizational performance. This is because the success shown through employee performance and supported by the effectiveness of optimal leadership, so that organizational performance can be achieved successfully. Every employee at the Maluku Province Education Office can work collectively as a unified entity in carrying out the interests of the organization, so that the resources of employees through the performance shown can be organized effectively in achieving organizational goals.